Self-empowerment and humanizing education in online teaching and learning – a personal journey - Zulkifli, Izyani (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
This chapter looks at a personal journey in humanizing education through self-empowerment in online teaching and learning. The experience is recorded from three semesters, starting in Semester 2, 2019-2020 when the COVID-19 pandemic first hits the nation until the most recent Semester 2, 2020-2021. In trying to humanize education on a personal level, we must try to empower ourselves to try new things and be flexible in adopting changes upon getting feedback. While it may be difficult to please all parties in online teaching and learning, we can try to humanize education by being flexible in our delivery of teaching and in the way we conduct our assessments.